MTHFR rs1801133 Gene Polymorphism and Autism Susceptibility - Mahsa Delshadpour (Caspian Journal of Neurological Sciences, 2017)
Background: It is believed that environmental and genetic factors may be responsible for autism. Methylenetetrahydrofolate reductase (MTHFR) and its gene polymorphisms have been shown to be implicated as risk factors in autism.